Ecological Psychology and Enactivism: A Normative Way Out From Ontological Dilemmas - de Pinedo García, Manuel (Frontiers in Psychology, 2020)
Two important issues of recent discussion in the philosophy of biology and of the cognitive sciences have been the ontological status of living, cognitive agents and whether cognition and action have a normative character per se. In this paper I will explore the following conditional in relation with both the notion of affordance and the idea of the living as self-creation: if we recognize the need to use normative vocabulary to make sense of life in general, we are better off avoiding taking sides on the ontological discussion between eliminativists, reductionists and emergentists. Looking at life through normative lenses is, at the very least, in tension with any kind of realism that aims at prediction and control. I will argue that this is so for two separate reasons. On the one hand, understanding the realm of biology in purely factualist, realist terms means to dispossess it of its dignity: there is more to life than something that we simply aim to manipulate to our own material convenience. On the other hand, a descriptivist view that is committed to the existence of biological and mental facts that are fully independent of our understanding of nature may be an invitation to make our ethical and normative judgments dependent on the discovery of such alleged facts, something I diagnose as a form of representationalism. This runs counter what I take to be a central democratic ideal: while there are experts whose opinion could be considered that last word on purely factual matters, where value is concerned, there are no technocratic experts above the rest of us. I will rely on the ideas of some central figures of early analytic philosophy that, perhaps due to the reductionistic and eliminativist tendencies of contemporary philosophy of mind, have not been sufficiently discussed within post-cognitivist debates.